2023
DOI: 10.3390/microorganisms11082103
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Recycling of Polylactic Acid Food Packaging Waste into Carboxylates via Hydrolysis and Mixed-Culture Fermentation

David P. B. T. B. Strik,
Brian Heusschen

Abstract: To establish a circular economy, waste streams should be used as a resource to produce valuable products. Biodegradable plastic waste represents a potential feedstock to be microbially recycled via a carboxylate platform. Bioplastics such as polylactic acid food packaging waste (PLA-FPW) are theoretically suitable feedstocks for producing carboxylates. Once feasible, carboxylates such as acetate, n-butyrate, or n-caproate can be used for various applications like lubricants or building blocks for making new bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…The resulting degradation products, such as monomers and oligomers, can serve as feedstocks for biopolymers, biofuels, and other value-added products, reducing dependence on fossil resources. In addition, enzymatic degradation helps reduce the environmental impact associated with the accumulation of synthetic fiber waste [19][20][21]. Bei et al investigated the enzymatic degradability of the three polyester types using cutinase and found that the biological degradability depends on the spacing of the ester groups and the crystallinity.…”
Section: Enzymatic Degradationmentioning
confidence: 99%
“…The resulting degradation products, such as monomers and oligomers, can serve as feedstocks for biopolymers, biofuels, and other value-added products, reducing dependence on fossil resources. In addition, enzymatic degradation helps reduce the environmental impact associated with the accumulation of synthetic fiber waste [19][20][21]. Bei et al investigated the enzymatic degradability of the three polyester types using cutinase and found that the biological degradability depends on the spacing of the ester groups and the crystallinity.…”
Section: Enzymatic Degradationmentioning
confidence: 99%